Multi‐Instrument Investigation of the Impact of the Space Weather Events of 6–10 September 2017 - Paul O. Amaechi; Andrew O. Akala; Johnson O. Oyedokun; K. G. Simi; O. Aghogho; Elijah O. Oyeyemi (Space Weather)
Abstract We analyzed the space weather events of 6–10 September 2017 using the multi‐instrument approach. We focused on the four X‐class flares which emanated from the Active Region AR 12673 and the Ground Induced Currents hazard associated with the geomagnetic storm of 7–8 September 2017. The flare effect on the equatorial electrojet (EEJ) recorded on board the SWARM satellite and on the horizontal component of the geomagnetic field (H) records of ground‐based magnetometers was further examined. During the X2.2/X1.3 flares of 6/7 September, the maximum percentage Global Navigation Satellite System (GNSS) vertical Total Electron Content (VTEC) increase was 6.9%/5.0% in Dakar/Porto Velho. During the X9.3/X8.2 flare of 6/10 September it was 7.9%/18.8% in Ascension Island/Kourou. The strongest Solar Flare Effect occurred in Mbour and Kourou during the respective flare. However, the highest EEJ increase was observed during the X2.2 and X9.3 flares. Interestingly, the X.9.3 flare resulted in a stronger ionospheric response than the X8.2 flare. Furthermore, global TEC map showed a higher response in the African and South American longitude during the respective event. The total radio fade‐out lasted from 30 to 90 min at the Hermanus and Sao Luis ionosondes during the flares, while the risk level to critical ground infrastructures based on the geomagnetically induced currents hazard was very low risk. Our results highlight the potential GPS positioning errors induced by sudden increase in TEC and the loss of high‐frequency communication and GNSS navigation signals associated with these solar events.